Alleviating the polysulfides "shuttling" and improving the sulfur utilization ably by the micropores of MOFs materials. (5th February 2021) - Fan, Chaojiang; Yang, Rong; Liu, Ying; Chen, Dan; Chen, Liping; Liu, Rui; Yan, Yinglin; Zou, Yiming; Xu, Yunhua
Summary: The irreversible capacity fade, low Coulombic efficiency and sulfur utilization rate caused by the "shuttle" of polysulfides are serious drawbacks of lithium sulfur (Li‐S) battery. Here, a regular octahedral structure and abundant hierarchical porous S/MIL‐101(Cr)‐H, as the electrode of Li‐S battery to catch and anchor polysulfides for alleviating the "shuttle effect" and strengthening the utilization of S, were synthesized by usual hydrothermal and facile heat treatment. Consequently, compared with S/MIL‐101(Cr) (719.52 mA h g −1 ), S/MIL‐101(Cr)‐H shows better initial discharge capacity (1073.59 mA h g −1 ) and the reversible capacity remains (446.59 mA h g −1 ) after 100 cycles at 0.1C, which is much greater than S/MIL‐101(Cr). A capacity of 504.26 mA h g −1 and Coulombic efficiency of approximately 95% at 0.5 C were obtained. The better electrochemical property is ascribed to the coordinated effect of the adsorption of microporous structure and chemical bonding of Cr‐S, which can effectively capture the soluble polysulfides and alleviate "shuttle effect" through physical confinement and chemical anchoring. Abstract : Efficient utilize of the microporous structure of MIL‐101 (Cr) achieves the dual effects of physical adsorption and chemical capture of polysulfides, which can alleviate the shuttle effect and increase the utilization of sulfur. Improve the electrochemical performance for lithium‐sulfur batteries and provide guidance for the research and application of MOFs materials to energy storage materials.